CBR Net :- Smart Technology over a Network - Doyle, Michelle; Hayes, Conor; Cunningham, Padraig; Smyth, Barry (Trinity College Dublin, Department of Computer Science, 1998)
CBR (case-based reasoning) has considerable potential for developing intelligent assistants for the World Wide Web. We examine intelligent applications already existent online and find that they can be divided into agent applications and thin client applications. Several case-based intelligent systems already exist on the web. These applications follow the thin client model with the intelligence located at the server side. In this paper we explore the advantages of distributing the processing load to the client side. We present an architecture for such a distributed CBR system for both an Internet and intranet application and describe how a case-representation language based on XML can facilitate this distribution. Adopting a standard case-representation language offers the possibility of communication between different applications, and agent-like interoperability.
Keywords: Computer Science